Melestarikan Warisan Budaya: Pengajaran Tari Tradisional Tari Rerere Kepada Generasi Muda Di Desa Sidorejo - Wapa, Andi; Wijakosno, Agus; Azizah, Siti Nur; Zakiya, Shela Rizki (Jurnal Pengabdian dan Pemberdayaan Banyuwangi (Jurnal Abdiwangi), 2024)
This community service aims to apply local wisdom skills by learning to dance Rerere in Sidorejo village, Rowokangkung District, Lumajang Regency. By using the training implementation method for children and teenagers at the service location with 11 times training and 1 time peak performance. In conclusion, the application of traditional dance is local wisdom that needs to be preserved, by transforming Rerere dance skills is a form of imparting education in the form of culture which is characteristic of the Indonesian nation. Rerere dance training was conducted in Sidorejo Village, Rowokangkung District, Lumajang Regency with participants ranging from children to teenagers. This implementation was prepared to welcome Indonesia's 79th Independent day, to be precise, August 17 2024.